On world literature’s frontier : Jules Verne and the portable printing press - Riordan, Kevin (2022)
Jules Verne read a lot of newspapers. In an 1895 interview he claimed to subscribe to twenty different periodicals (Belloc 1985). In another interview, he detailed his daily routine in his study: